Theoretical conceptions of evolution of adjusting insurance activity mechanism in Ukraine - Калюжний, Ростислав Андрійович; Заєць, Олександр Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The analysis of theoretical conceptions of evolution of adjusting insurance activity mechanism in Ukraine is done. The necessity of study the evolution of adjusting insurance activity mechanism in Ukraine is marked. It is mentioned that such a study will help to be oriented in processes that take place at the insurance market, forecast its progress trends, build relations taking into account the historical experience, obtained in centuries-old history of foreign and national insurance. On the first stages of the development of analyzed institution, only narrow range of risks were under insurance, insurance pavements were not regular. Soon there appear new kinds of insurance, polis form of insurance contract, insurance mediation is being developed, special financial organizations that provide insurance services are created. There is a remarkable expression of academian V. K. Voblyi who said in 1923 that “…history of insurance business is natural and undeniable part of insurance economics. Only studying history we can correctly examine and understand the current condition of insurance business.” Despite the fact that forms and methods of insurance have changed under the development of historical, economic and social relationships, nowadays they could be considered as a prototype of insurance market forms that appeared and are being developed today in Ukraine. Such approach’s realization gives an opportunity to adjust the existing legislation and to decrease a criminal situation in this area, to create a reliable mechanism to protect the interests of the insurance market subjects.